PENGARUH TAX AVOIDANCE, KEBIJAKAN DEVIDEN, DAN AGENCY COST TERHADAP NILAI PERUSAHAAN SEKTOR MAKANAN DAN MINUMAN - Anggik Firda Safara; Tania Apriliyanti; Aminatuzzuhro Aminatuzzuhro (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2024)
The purpose of this study was to determine whether Tax avoidance, Dividend Policy, and Agency cost have a significant effect on firm value in manufacturing companies listed on the IDX 2020-2023. This study uses a descriptive quantitative approach which aims to explain the effect of the independent variables, namely Tax avoidance, Dividend Policy, and Agency cost on the dependent variable, namely firm value. The analysis method used in this study is multiple linear regression analysis, partial test (t test), coefficient of determination (R2 test) and simultaneous F test. The results of multiple linear regression analysis show that the three variables (X) show a positive effect on the variable (Y). The result of the partial test (t test) shows that all variables (X) have a significant effect on variable (Y). The result of R2 test shows that variable (Y) is influenced by variable (X) of 42.9% and the remaining 51.7% is influenced by other variables not examined in this study. And the simultaneous F test shows that variable (X) has a significant effect on variable (Y).